2012 Sixth International Conference on Next Generation Mobile Applications, Services and Technologies 2012
DOI: 10.1109/ngmast.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Always Best Packet Switching Mechanism

Abstract: Abstract-In this work we investigate the performance of the Always Best Packet Switching (ABPS) operation approach. ABPS is a cross-layer wireless communication scheme that enables mobile terminals to exploit its multiple Network Interface Cards (NICs) concurrently. The ABPS software module installed on the mobile terminal determines dynamically the most appropriate NIC to use as single point of access to the Internet, and can switch to another NIC dynamically and transparently to the applications. For the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A prototype implementation of ABPS is available [3], and supports interactive multimedia services based on SIP/RTP/RTCP. In [1] we have shown that our approach provides better performance in terms of availability, reliability and throughput, with respect to conventional wireless communication services. In [2] we studied the power consumption of ABPS: our analysis revealed that, under some realistic conditions, ABPS requires less energy than traditional single NIC systems, and other classic Session Initiation Protocol (SIP)-based multi-NIC communication approaches.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A prototype implementation of ABPS is available [3], and supports interactive multimedia services based on SIP/RTP/RTCP. In [1] we have shown that our approach provides better performance in terms of availability, reliability and throughput, with respect to conventional wireless communication services. In [2] we studied the power consumption of ABPS: our analysis revealed that, under some realistic conditions, ABPS requires less energy than traditional single NIC systems, and other classic Session Initiation Protocol (SIP)-based multi-NIC communication approaches.…”
Section: Introductionmentioning
confidence: 92%
“…Availability and reliability of ABPS have been studied in [1], while power consumption has been investigated in [2]. A particular aspect of ABPS is that a software module at the MN continuously monitors all the NICs and probes the communication channels looking for access points to connect to.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is very important to note that, commonly, the unavailability time interval does not include the handover time only. When a network becomes unavailable (and thus a handover is required) there is a time interval during which the NIC appears to be functioning (at the MN), but packets are lost [98]. Then, the MN only detects that the connection with its access points has been lost after a while and eventually the handover begins.…”
Section: Performancementioning
confidence: 99%
“…Similarly, those architectures where handovers may fail (see the discussion of the unavailability interval above) may provide a low level of service continuity. Finally, the maximum continuity interval is provided by solutions based on the early packet loss detection; this is due to the fact that these approaches may recover from packet losses by switching to (and retransmitting through) a different NIC [98].…”
Section: Performancementioning
confidence: 99%